The Stability and Growth Pact in Practice: inefficiencies of previous debt rules and the way forward - Ionut Jianu; Maria-Daniela Tudorache (Theoretical and Applied Economics, 2024)
This paper aims to assess the compliance of the EU Member States with the previous debt rules over the period 2011-2023. To achieve this, we assessed two complementary criteria concerning public debt, respectively the compliance with the 60% of GDP threshold and the one related to the debt reduction rule, which indicates that Member States with public debt levels higher than 60% of GDP should reduce the difference between the level of public debt share in GDP and the 60% of GDP threshold with an average rate of 1/20 in the last three years. Further, we highlighted the reasons why the last economic governance framework was not effective and we presented the new debt rules in their revised form.
Keywords: E62; E63; H62; H63; 330; Stability and Growth Pact; public debt; rules; fiscal; economic governance review